Effectiveness of delivery mode of pharmacist intervention to improve medication adherence and clinical outcomes in people with depression: a systematic review - Yosi Febrianti; Ika Puspita Sari; Anna Wahyuni Widayanti; Diana Setiyawati (Intelektual Pustaka Media Utama, 2026)
Depression is a treatable mental health condition with various medication options available. For patients with major depressive disorder (MDD), adherence to antidepressants is essential for effective treatment. However, low medication adherence remains a significant challenge, particularly in individuals with depression. Pharmacists play a crucial role in managing these patients. This systematic review evaluated the impact of pharmacist-led interventions, focusing on the effectiveness of delivery modes (in-person vs. online) in improving medication adherence and clinical outcomes for patients with depression. Randomised and non-randomised controlled trials were included. Data were sourced from PubMed, Scopus, ScienceDirect, and Google Scholar using keywords such as